Key Issues in Implementing CLT in EST - Mouna, HEZBRI; Djamel, GOUI (جامعة الوادي - University of Eloued, 2021)
This study attempts to identify the reasons behind the failure of communicative language teaching (CLT) in developing a high level of EL oral proficiency among EFL learners in oral expression classes. Through investigating the key issues of implementing its techniques and strategies in English speaking teaching (EST), it highlights the deficiencies of this method in effectuating an effective didactical oral experience; whereby, EFL learners are able to acquire English speaking skills and develop an independent EL communicative competence (CC) so as to meet their needs in communicating more efficiently using EL. In this respect, it also seeks to reduce the effects of these deficiencies via suggesting alternative implications for English speaking skills didactics in oral expression classes. As well as increasing its efficiency in order that a higher English oral proficiency would be available for EFL learners in oral expression classes, eventually.
مقال
Keywords: CLT; EST; English Speaking Skills; Oral Expression Lessons.